Is Hyperthyroidism a Possible Etiology of Early Onset Dementia? - Joy Mathew, Christopher (Cureus, 2020)
Dementia, a disabling syndrome of the elderly characterized by the decline in memory and cognition, is increasing in incidence and affects not only the individual but also their family and close ones. Hyperthyroidism can mimic many other diseases and untreated hyperthyroidism can lead to adverse problems of various systems including the heart, bones, muscles, menstrual cycle, and fertility. In this article, we have tried to evaluate the association between hyperthyroidism and dementia, as well as the impact of hyperthyroidism management in the treatment and prevention of dementia. Studies available in the PubMed database have been used, excluding animal studies and including studies of adults above the age of 50. The analysis of studies reveals that thyroid dysfunction can lead to cognitive impairment. It has not been able to prove that hyperthyroidism can lead to an earlier onset of dementia. But subclinical hyperthyroidism, thyroid-stimulating hormone (TSH) levels below the normal range, and high free thyroxine (T4) levels increase the risk of dementia among the elderly. The possible mechanisms involved in this association have also been discussed. Thus, we concluded that it is essential to detect and manage hyperthyroidism at an earlier stage since hyperthyroidism increases the risk of dementia. The possibility of using antithyroid treatment in euthyroid dementia is yet to be studied extensively.